Estimasi Proporsi Kesalahan Fonologi Pada Anak Pendidikan Anak Usia Dini (PAUD) Usia 3-5 Tahun Di Surakarta - Dewi Tirtawati; Kiyat Sudrajat (Interest : Jurnal Ilmu Kesehatan, 2019)
Background : Language acquisition skills talk to a child is most important because it is closely related to the phonology ability and relates to the ability of semantic and syntax acquisition. Children who experience Keretlambatan speaking language are at risk of learning difficulties, difficulty in reading and writing and will lead to less thorough academic achievement, this can continue to be young. Thus, the need for early detection of the phonological ability will be seen as a result of the estimated proportion of the phonological errors in the child. Methods: This research uses the survey method. Research location in PAUD Al-Kautsar and PAUD Budi Karya Mojosongo Surakarta. With samples of PAUD children aged 3-5 years, 45 children with independent variables are phonological errors and their variable dependencies are phonological errors, with technical Purposive sampling. The technique of collecting observation data with articulated observation sheet with a word-level image. Results: That there are 16 children or 34.04% of 47 samples with an estimated proportion of 20,50 < π < 47,59 of PAUD Children at the age of 3-5 who have phonological pronunciation errors.That PAUD children at the age of 3-5 who had the misspelling of phonology of female sex, more percentage of his phonological error, which is as much as 9 children (56,25%) With an estimate of the proportion of 42.07 < π < 70.43 compared to boys, as many as 7 children (43,75%) With an estimate 29.57 < π < 57.93. Conclusion: There are phonological errors in children aged 3-5 years old, but based on his/her age is still in the process of phoneologically (Phonological Prosesses).